(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Purpose, task, means of physical education. The goals and tasks of physical education in educating the young generation in a healthy, well-rounded spirit are of great importance in the education of our youth. In the current period, advanced development in the conditions of technical development requires high mobility of the organism’s function. It requires the ability to respond clearly and quickly, strong-willed, trained, courageous, resilient people who are not afraid of difficulties. The goal of physical education is a healthy lifestyle, physical fitness, preparation for the defense of the country, life and work. This goal is the same, for all institutions and organizations that carry out physical education of people in our country